Obstetrics and gynecology - Pfeifer, Samantha M. (National medical series for independent study, 2012)
"The book provides up-to-date and relevant information in an easy-to-understand outline format for both students and residents. Basic scientific information is balanced by clinical relevance, and a wealth of more than 200 USMLE-formatted questions allows readers to test their knowledge prior to their board examinations"